First record of the intertidal dwarf bug family Omaniidae from China, with description of a new species (Heteroptera: Leptopodomorpha) - Luo, Jiu-Yang; Wang, Yan-Hui; Chen, Ping-Ping; Xie, Qiang (Zootaxa, 2022)
A new intertidal dwarf bug, Corallocoris xishaensis Luo, Wang & Chen sp. nov., from Xisha Islands of South China Sea is described, and is the first record of the family Omaniidae Cobben, 1970 from China. The new species can be distinguished from its allied Austro-Oriental species C. marksae (Woodward, 1958) by the colour of its body and legs, and the genitalic structures of both sexes. Photographs of the habitus, head, thorax, abdomen, appendages and genitalic structures are provided, additional scanning electron micrographs of the body surface are presented as well. A key to all the species of Omaniidae and distributional maps based on the known records for all species of this family are provided.